Experimental and numerical studies on model updating method of damage severity identification utilizing four cost functions. Issue 1 (10th August 2011) - An, Yonghui; Ou, Jinping
SUMMARY As the final stage of damage identification, damage severity identification has great significance to structural safety assessment and decision‐making in maintenance. Take the damage detection of truss structures for instance; the stochastic damage locating vector method has great advantages. However, the method is a localization technique designed to provide information in damage location only. Many present damage severity identification methods suffer from great error due to high noise. Therefore, it is imperative to develop a new identification method for truss structural health monitoring. To solve this problem, this paper presents the model updating method of damage severity identification based on four cost functions: (i) correlation coefficient of free vibration accelerations; (ii) correlation coefficient of local mode shapes; (iii) free vibration accelerations assurance criterion; and (iv) local modal assurance criterion. In these functions, correlation coefficient and correlation degree of free vibration accelerations of measured nodes are first proposed to identify damage severity. Moreover, a simple supported bailey steel‐truss bridge Benchmark Model has been designed and constructed. The span is 8 m with the scaled ratio 1:25. Based on the model, both experimental and numerical simulation results using these procedures under pulse excitation indicate that they are feasible and effective. In addition, the proposed techniques exhibit high‐noise insusceptibility. Copyright © 2011 John Wiley & Sons, Ltd.